Internalisasi Nilai-Nilai Pendidikan Akhlak dalam Pembelajaran Pendidikan Agama Islam di Era Digital di SDN 17 Manggis Ganting Bukittinggi - Nita Damayani; Mustafa (YASIN, 2026)
The internalization of moral education values in Islamic Religious Education (PAI) learning faces various challenges in the digital era, particularly the negative influence of social media, low awareness of religious observance, limited parental supervision, and the suboptimal development of students’ character through religious activities at school. This study aimed to analyze the process of internalizing moral education values in PAI learning at SDN 17 Manggis Ganting and to identify its supporting and inhibiting factors. The study employed a qualitative approach with a descriptive design. The informants consisted of PAI teachers and students selected purposively. Data were collected through observation, semi-structured interviews, and documentation and were then analyzed through data reduction, data presentation, and conclusion drawing. Data validity was established using source triangulation. The findings showed that the internalization of moral education values was implemented through three stages: value transformation, value transaction, and value transinternalization. The values instilled encompassed moral conduct toward Allah, oneself, and others. This process was supported by teachers’ exemplary conduct, religious programs, cooperation between the school and parents, and the use of digital media in learning. Meanwhile, the negative influence of social media, insufficient parental supervision, students’ low self-awareness, and their social environment constituted inhibiting factors. This study concludes that the internalization of moral education values has been implemented progressively and integrated into PAI learning, but its sustainability requires synergy among schools, families, and communities. These findings provide practical implications for strengthening PAI learning strategies that are adaptive to digital developments and oriented toward students’ character development.